2010
DOI: 10.1007/s12630-009-9233-4
|View full text |Cite
|
Sign up to set email alerts
|

Routine preoperative electrocardiogram and chest x-ray prior to elective surgery in Alberta, Canada

Abstract: Routine preoperative testing rates and costs are relatively low in Alberta. It is possible that general evidence widely disseminated over the past number of years regarding unnecessary routines in preoperative testing has had an effect. Further interventions to reduce them would be of little value.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 10 publications
0
9
0
1
Order By: Relevance
“…Thanh and colleagues 20 found that rates of testing before elective noncardiac sur gery were 13.4% for ECG and 23.2% for chest radiography. Similarly, in a study of the Medi care population in the United States, Sheffield and associates 21 found that the rate of stress test ing before low and intermediaterisk surgery was 6.4%.…”
Section: Discussionmentioning
confidence: 99%
“…Thanh and colleagues 20 found that rates of testing before elective noncardiac sur gery were 13.4% for ECG and 23.2% for chest radiography. Similarly, in a study of the Medi care population in the United States, Sheffield and associates 21 found that the rate of stress test ing before low and intermediaterisk surgery was 6.4%.…”
Section: Discussionmentioning
confidence: 99%
“…There has been a large body of work reporting pre-operative testing practices [2,4,6,10,31-33]. However, few attempt to explain why clinicians do one thing when the guidelines recommend another with respect to test ordering for anesthesia management [7].…”
Section: Discussionmentioning
confidence: 99%
“…Further the anesthesiologists and surgeons interviewed appear to lend credence to this report. Yet, reports continue to document unnecessary routine test ordering [2,4,6,10,31-33], and we have attempted to ask those clinicians involved why unnecessary tests for anesthesia management continue to be ordered. Bryson et al was the only paper reviewed to suggest a need to change ‘ established behaviour ’ that should include not only anesthesiologists but surgical colleagues and clinic personnel [10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Routine tests rarely alter the clinical management of the case and may end up exposing the patient to radiation, causing discomfort and generating unnecessary costs (Bordage, 1995;Garcia-Miguel and Serrano Aguilar, 2003;Mantha et al, 2005;Bryson et al, 2006;Fattahi, 2006;Thanh and Jonsson, 2010). Extra tests may also increase medical-legal liability, as up to 60% of the abnormalities detected in the preoperative period are not investigated (Wagner and Moore, 1991;Roizen, 1989Roizen, , 2000.…”
Section: Introductionmentioning
confidence: 99%